2020
DOI: 10.1149/1945-7111/abd0cc
|View full text |Cite
|
Sign up to set email alerts
|

Selective Permeation of Dysprosium Through an Alloy Diaphragm in Molten Chloride Systems

Abstract: To develop a new separation technique for rare earth (RE) elements based on alloy diaphragms and molten salt electrolysis, a permeation experiment was conducted in LiCl–KCl eutectic melts containing RECl3 (RE = Dy, Nd, and La, 0.5 mol%) at 450 °C. In this technique, the alloy diaphragm functions as a bipolar electrode and RE ions permeate via three steps: (a) reduction of RE ions to form alloys on the anolyte side of the diaphragm, (b) diffusion of RE atoms in the diaphragm, and (c) oxidation of RE atoms to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…During electrolysis, RE ions were oxidized and dissolved in the anode chamber, and specific RE element alloys were formed, which diffused through the IG diaphragm; finally, the RE metal was recovered at the cathode. Our previous studies confirmed that RE-Ni alloys (RE = Pr, Nd, Dy) are selectively formed via electrolysis by utilizing Ni-based substrates in the following molten electrolytes: LiCl-KCl-RECl 3 at 723 K, [12][13][14][15][16] NaCl-KCl-RECl 3 at 973 K, [17][18][19][20] and LiF-CaF 2 -REF 3 at 1123 K. 19,[21][22][23][24][25] In addition, this process exhibits a high RE separation ability over a specific potential range. However, the brittle nature of RE-Ni alloys results in durability issues in the alloy diaphragms.…”
supporting
confidence: 62%
“…During electrolysis, RE ions were oxidized and dissolved in the anode chamber, and specific RE element alloys were formed, which diffused through the IG diaphragm; finally, the RE metal was recovered at the cathode. Our previous studies confirmed that RE-Ni alloys (RE = Pr, Nd, Dy) are selectively formed via electrolysis by utilizing Ni-based substrates in the following molten electrolytes: LiCl-KCl-RECl 3 at 723 K, [12][13][14][15][16] NaCl-KCl-RECl 3 at 973 K, [17][18][19][20] and LiF-CaF 2 -REF 3 at 1123 K. 19,[21][22][23][24][25] In addition, this process exhibits a high RE separation ability over a specific potential range. However, the brittle nature of RE-Ni alloys results in durability issues in the alloy diaphragms.…”
supporting
confidence: 62%
“…14 Therefore, in our ongoing research on selective permeation through an alloy diaphragm, we have been most intensively investigating Ni and Ni-based alloys. [7][8][9][10][11][12][13] Recently, we reported selective permeation of Dy through an RE-Ni alloy diaphragm in molten LiCl-KCl eutectic melts containing NdCl 3 and DyCl 3 at 450 °C. 12 However, selective permeation of Nd is indispensable for realizing the recycling process shown in Fig.…”
Section: Re Anolytementioning
confidence: 99%
“…1). [7][8][9][10][11][12][13] This process entails the use of RE-IG (IG = Fe, Ni, and Co) alloy diaphragms for the separation of the REs in molten salts. 7 The RE-IG alloy diaphragm acts as a bipolar electrode and RE ions permeate through three steps: (a) reduction of the RE ions to form an alloy on the anolyte side of the diaphragm according to reaction 1, (b) transportation of RE atoms in the diaphragm, and (c) oxidation of the RE atoms that dissolve into the catholyte as RE ions on the other side of the diaphragm according to reaction 2.…”
mentioning
confidence: 99%
“…Thus, it is necessary to develop an inexpensive and effective recovery/separation process of Dy from scraps of the Dy-added Nd-Fe-B magnet. From this background, we have been investigating a new recovery process of Dy and Nd from the magnet scraps using molten salt electrolysis and alloy diaphragms (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The key step in this process is the alloying and de-alloying of rare earth (RE) elements on both sides of the diaphragm in order to effectively separate them in the molten salt.…”
Section: Introductionmentioning
confidence: 99%